Healthcare Resource Utilisation of Severe Uncontrolled T2low and Non-T2low Asthma in Finland During 2018-2021 - Persson, Josefine; Aakko, Juhani; Kaijala, Saara; Lassenius, Mariann; Viinanen, Arja; Kankaanranta, Hannu; Lehtimäki, Lauri (Dove Medical Press, 2025)
Purpose: Patients with asthma and low levels of type 2 inflammatory biomarkers (T2 low) have limited effective treatment options. Such biomarkers include eg blood eosinophils (b-eos) and fractional exhaled nitric oxide (FeNO). The healthcare resource utilisation (HCRU) of severe uncontrolled T2 low asthma remains unexplored. Thus, this study aimed to estimate the HCRU of T2 low and non-T2 low severe uncontrolled asthma patients using real-world data in Finland.
Patients and methods: Adult patients with an asthma diagnosis during baseline (2012-2017) at the pulmonary department of Turku University Hospital were included and followed during 2018-2021, or until death. Total HCRU costs and respiratory-related HCRU costs were evaluated. The main drivers for the HCRU and costs were assessed with gamma and negative binomial regression models.
Results: Of the severe uncontrolled asthma patients with T2 status available, 40% (N=66) were identified with T2 low and 60% (N=103) with non-T2 low asthma. The average cumulative cost per patient was similar in patients with T2 low compared with non-T2 low, with all-cause costs cumulating in four years of follow-up to 37,524€ (95% CI: 27,160, 47,888) in T2 low compared to 34,712€ (25,484, 43,940) in non-T2 low. The corresponding average cumulative respiratory-related costs were 5178€ (3150, 7205) in T2 low compared to 5209€ (4104, 6313) in non-T2 low. Regression modelling identified no differences between the T2-status groups when assessing all-cause healthcare costs per patient-year (PPY). On the other hand, the regression modelling predicted more inpatient days PPY for severe uncontrolled patients with T2 low status compared to the patients with non-T2 low status.
Conclusion: Patients with uncontrolled severe T2 low asthma use equal healthcare resources as corresponding non-T2 low patients. This study brought new insights into the HCRU of severe uncontrolled asthma patients per T2 status, which has not previously been investigated.